Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan pada Perusahaan Umum Daerah Air Minum Kota Makassar - Kasibit, Fitriyani; Hasbiah, Sitti; Ruma, Zainal (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to find out how leadership style influences employee performance at the regional public water company in Makassar City. The independent variable in this research is leadership style while the dependent variable is employee performance. For data collection, 93 workers of the Makassar City Regional Public Drinking Water Company were given questionnaires and supporting materials. This research uses a quantitative research design. The population in this study was 1,357 people and a sample of 93 people was selected using simple regression analysis using (SPSS) version 25 and Microsoft Excel. The results of this research show that leadership style has a positive and significant effect on employee performance. Hypothesis test results with the help of the SPSS version 23 application by carrying out the T test.